2013
DOI: 10.1590/s0103-51502013000100016
|View full text |Cite
|
Sign up to set email alerts
|

Lower-limb endurance training program influences thoracoabdominal motion of patients with COPD?

Abstract: INTRODUCTION: Thoracoabdominal-TA asynchrony is an important sign of Chronic Obstructive Pulmonary Disease (COPD). Studies investigating the influence of endurance training on TA asynchrony have not been found. OBJECTIVE: To analyze lower-limb endurance training effects on TA asynchrony in patients with COPD. MATERIALS AND METHODS: Two patients with severe COPD were evaluated in a single-subject design AB (A-baseline for six weeks, B-training on cycle ergometer with intensity of 70% of baseline peak load, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This finding corroborated reports of some studies of subjects with COPD that found increases in asynchrony during diaphragmatic breathing, 10,13,29,30 which seem to be related to (1) the sitting position assumed for the evaluation (a higher trunk elevation favors greater asynchrony in subjects with COPD), 29 (2) the voluntary changes in the breathing pattern assumed during the breathing exercises (even for healthy subjects, the spontaneous breathing pattern presents asynchrony), 38 and (3) the greater focus on the use of the diaphragm (according to the instructions for diaphragmatic breathing and diaphragmatic breathing plus pursed-lips breath-ing) performed by subjects with biomechanical impairment of this muscle when considering that they have a respiratory overload while performing any type of exercise. 30,39 Both breathing exercises promoted a decrease in the breathing frequency due to the increase of inspiratory time and expiratory time. Those changes in breathing pattern supported the findings of previous studies of the effects of diaphragmatic breathing and pursed-lips breathing assessed separately.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborated reports of some studies of subjects with COPD that found increases in asynchrony during diaphragmatic breathing, 10,13,29,30 which seem to be related to (1) the sitting position assumed for the evaluation (a higher trunk elevation favors greater asynchrony in subjects with COPD), 29 (2) the voluntary changes in the breathing pattern assumed during the breathing exercises (even for healthy subjects, the spontaneous breathing pattern presents asynchrony), 38 and (3) the greater focus on the use of the diaphragm (according to the instructions for diaphragmatic breathing and diaphragmatic breathing plus pursed-lips breath-ing) performed by subjects with biomechanical impairment of this muscle when considering that they have a respiratory overload while performing any type of exercise. 30,39 Both breathing exercises promoted a decrease in the breathing frequency due to the increase of inspiratory time and expiratory time. Those changes in breathing pattern supported the findings of previous studies of the effects of diaphragmatic breathing and pursed-lips breathing assessed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Lower torso training in asthma patients is essential to improve the respiratory system and muscle function and reduce dyspnea. Some studies showed that training a lower limb reflects thoracoabdominal motion and significantly decreases dyspnea and other variables [ 13 ]. There is strong evidence that leg exercise performance decreases dyspnea and leg fatigue in patients with a respiratory system.…”
Section: Introductionmentioning
confidence: 99%